GOVERNMENT SPENDING (ECONOMY, SOCIAL PROTECTION, HEALTH, EDUCATION) ON INCOME INEQUALITY IN WEST JAVA - Prannisa, Alfath; Muljarijadi, Bagdja; Wardhana, Adhitya (TRIKONOMIKA, 2023)
This study aims to examine the effect of government spending on the economy, social protection, health, and education on income inequality in West Java during 2015-2020. Income inequality in this study uses the Gini ratio. The estimation uses a fixed effect panel data model using the cross-section weight (EGLS) method. The results show that government spending contributes to reducing income inequality in West Java in 2015-2020. Meanwhile, control variables such as GRDP per capita and poverty have a significant effect on increasing income inequality and investment variables have a significant effect on reducing income inequality.